1998
DOI: 10.1038/sj.bmt.1701486
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, blinded, placebo-controlled, dose escalation study of the tolerability and efficacy of filgrastim for haemopoietic stem cell mobilisation in patients with severe active rheumatoid arthritis

Abstract: Summary:Autologous haemopoietic stem cell transplantation (HSCT) represents a potential therapy for severe rheumatoid arthritis (RA). As a prelude to clinical trails, the safety and efficacy of haemopoietic stem cell (HSC) mobilisation required investigation as colony-stimulating factors (CSFs) have been reported to flare RA. A double-blind, randomised placebo-controlled dose escalation study was performed. Two cohorts of eight patients fulfilling strict eligibility criteria for severe active RA (age median 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(55 citation statements)
references
References 44 publications
1
51
0
3
Order By: Relevance
“…Usually, mobilization is preceded and facilitated by chemotherapy (e.g., Cy). G-CSF administration has been associated with induction of flares of the underlying autoimmune disease) (27,28).…”
Section: Granulocyte Colony-stimulating Factor-associated Side Effectsmentioning
confidence: 99%
“…Usually, mobilization is preceded and facilitated by chemotherapy (e.g., Cy). G-CSF administration has been associated with induction of flares of the underlying autoimmune disease) (27,28).…”
Section: Granulocyte Colony-stimulating Factor-associated Side Effectsmentioning
confidence: 99%
“…32 An Australian study has reported flares of RA in patients receiving G-CSF for progenitor cell mobilization. 33 In contrast, one report in patients with RA and another in patients with SSc conclude that G-CSF may be given without a flare. 34,35 The patients with RA were pre-treated with corticosteroids which may have prevented disease exacerbation.…”
Section: Discussionmentioning
confidence: 88%
“…2) No segundo estudo, foram comparadas as doses de 5 e 10µg/kg/d de G-CSF, isoladamente, para mobilização de CTH. A dose maior de G-CSF foi associada com maior freqüência de reativação da AR, mas foi escolhida para futuros estudos em decorrência de sua maior eficiência (47) . 3) Um outro estudo comparou doses de 100 e 200mg/kg de CY, também isoladamente, para o condicionamento de pacientes submetidos a TCTH não manipulado.…”
Section: Artrite Reumatóide Do Adultounclassified